‘It’s Girl Time’: Girliness and Friendships - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
With what Chatterton and Hollands call the ‘ritual descent’ (2002: 95) of young women into bars and clubs every weekend, we must take seriously young women’s participation in such spaces and explore further what role participating in the NTE plays in young women’s lives. Participating in the NTE has been increasingly recognised as an important component of the lives of many young women (Hollands 1995), and the participants in my study were no exception. Set against a backdrop of conflicting debates positioning the NTE as simultaneously a site of both pleasure and regulation, it is important to understand the value engaging with the NTE has for young women and the ways in which this can offer opportunities for ‘doing’ femininities or girliness and cementing friendships within these spaces. The girls’ night out represents a discreet and distinctive mode of engagement with the NTE, yet one that has received little attention in research, despite the fact that it is likely to reveal a huge amount about the individual and collective production and negotiation of femininities and friendships in nightlife venues. This chapter provides the backdrop for the remainder of the book by exploring what the girls’ night out means to young women and the central role it can play in the negotiation and maintenance of friendships and in doing ‘girly’. Whilst previous research has depicted friendships within the NTE as potentially shallow or instrumental and consumption practices as highly individualised, this chapter highlights the ways in which going out was described as an important and valued opportunity to maintain close female friendships, spend time together and enjoy opportunities to socialise and relax. I will also introduce some of the ways in which alcohol consumption was central to the young women’s negotiations of the NTE. Drinking could take on a particular role on the girls’ night out, where alcohol could function in the maintenance and cementing of friendships and the creation of intimacy (particularly when ‘pre-drinking’ at home). Consuming certain types of alcohol could also enable ‘girliness’ to be embodied in particular ways through certain consumption choices. I argue that the ‘girling’ of drinking and clubbing is particularly significant because alcohol consumption in public spaces has traditionally been recognised as a masculine pastime, rendering drinking and femininity fundamentally incompatible. If young women are able to rupture the linkages between public drinking and masculinity, they may be able to recast women’s presence and alcohol consumption in the contemporary NTE as feminine and respectable. I also explore the ways in which getting ready for a girls’ night offered further opportunities to do girliness collectively.
Keywords: Female Friends; Girlhood; Girly Girl; Time Girls; wineWine

Conclusion - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
As has become increasingly evident throughout this book, the girls’ night out clearly offers specific and nuanced ways in which to do femininities and friendships which are not present in other types of night out, and perhaps also specific types of pressures to do femininity. Whilst the NTE is increasingly recognised as a useful avenue through which to research young people’s lives, less attention has been given to the girls’ night out as a specific type of engagement with the NTE that may illuminate nuances in the ways in which young women ‘do’ gender and femininities. This book thus marks a unique contribution within a wider body of research on young people’s drinking and clubbing. This concluding chapter will pull together the main arguments outlined throughout this book, highlighting the tensions and contradictions embedded in young women’s negotiations of femininity and the ways in which these reflect the idea that the successful embodiment of ‘girly’ and ‘girliness’ is simultaneously something that is desired yet derided.
Keywords: Drinking Practices; Girly Girl; Research Young People; Time Girls; otheringOthering